PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KOMITEN KARYAWAN YAYASAN BUKIT DOA MEDAN - Handi Joshua Pandia (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is to know (1) the effect of work environment on organizational commitment, (2) the effect of motivation to organizational commitment, (3) the most dominant variables affect the commitment of employee organizations. This research belongs to the type of quantitative research. The variables in this study are work environment, motivation, and employee organizations. The research population is all employees in the field of narcotics at Yayasan Bukit Doa Medan, while the research sample is 30 employees. Sampling technique in this research use saturated sampling (census). Data collection methods used questionnaires (questionnaires), while data analysis techniques used multiple regression analysis. The result of regression analysis obtained by linear double regression equation for two predictors is Y = 12,570 - 0,013 X1 + 0,641 X2 + e. The results showed (1) There is a not positive influence of work environment on employee organizations in field of narcotics at Yayasan Bukit Doa Medan with significant value (p) = 0,921>0,05. (2) There is a positive influence of motivation on employee organizations in field of narcotics at Yayasan Bukit Doa Medan with significant value (p) = 0,000<0,05. (3)The work environment has no effect on organizational commitment while work motivation has a signifficant effect on organizational commitment .The value of determinant coefficient (R2) between X1, and X2 with Y is 0,355, it means that the influence between work environment (X1) and motivation (X2) on employee organization (Y) is 35,5%.